2022
DOI: 10.3390/jcm11041145
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Features of Herd Immunity: Similarities in Age-Specific Anti-Measles Seroprevalence Data between Two Countries of Different Epidemiological History

Abstract: (1) Background: Measles immunization gap(s) raise the concern of potential outbreaks. Both Croatia and Hungary are situated in the vicinity of measles-endemic countries. Potentially compromised immunization activities due to the COVID-19 surge is a ground for concern. Our aim was to compare age-stratified seroprevalence results in the cross-border region. (2) Methods: Anti-MMR specific antibody levels (IgG) of 950 anonymous Croatian samples were compared with previous Hungarian results (n > 3500 samples), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 20 publications
5
10
0
Order By: Relevance
“…This demographic cluster likely experienced natural infections either during the early stages of vaccination or before widespread vaccination efforts were implemented. Our observation aligns with the established literature suggesting that immune protection resulting from wild-type infection elicits a more durable and robust immune response compared to vaccine-induced immunity [35,66,69,70,[80][81][82][83][84][85].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This demographic cluster likely experienced natural infections either during the early stages of vaccination or before widespread vaccination efforts were implemented. Our observation aligns with the established literature suggesting that immune protection resulting from wild-type infection elicits a more durable and robust immune response compared to vaccine-induced immunity [35,66,69,70,[80][81][82][83][84][85].…”
Section: Resultssupporting
confidence: 91%
“…The conspicuous deficit in humoral antibody titers and subsequent existence of seropositivity gaps within this age cohort prompt inquiries into vaccine efficacy [24,30,37,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. These findings echo previous studies [35,66,67,[69][70][71] and data in the literature [72][73][74][75][76][77][78][79], indicating persistent challenges in achieving sufficient immunity against measles despite vaccination efforts.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Recently, in the study conducted in the frame of the CABCOS3 project, it was reported that the Hungarian serum samples and Croatian serum samples were largely overlapping in seropositivity ratios, which might be attributed to the intrinsic biological dynamics of vaccination-based humoral immunity to measles. Individuals 34–43 years old had the lowest seropositivity ratios (78%) [ 34 ]. A prospective study conducted in Prague, Czechia, on a total of 2782 participants aged 19–89 years, analyzed the level of measles-specific antibodies in serum samples and showed that the seropositivity rate in naturally immunized participants (before 54 years) was significantly higher than in fully vaccinated persons aged 19–48 (98.0% (95% CI: 96.5–99.0%) vs. 93.7% (95% CI: 92.4–94.9%)).…”
Section: Discussionmentioning
confidence: 99%